Application of Urban Hydrology Model and Green Design for the Drainage System of Ha Tinh City - Quang Hung, Nguyen; Lien, Nguyen Thị (VNU Journal of Science: Earth and Environmental Sciences; Vol 37 No 3, 2021)
Ha Tinh is recently awarded the certification of second-class city, along with strong socio-economic development, meanwhile, infrastructure issues are still a matter required proper investment. In the past 5 years, despite being invested to expand and renovate urban drainage systems, floods remain and tend to be more complicated. In this study, Mike Urban software with  a two-dimensional simulation approach has been applied to Ha Tinh city to identify specific causes of flooding. Three scenarios to calibrate and validate model confirmed the correctness and practical ability of the urban hydrological model. In the context of climate change, scenarios show that without timely measures the drainage system will be overloaded even with low emission scenarios RCP4.5. In addition, two proposals with green design approach show that it is feasible to reduce floods with low cost and sustainability.